Postoperative opioid prescribing patterns and use after vascular surgery. (February 2019) - Colton, Ilsley B; Fujii, Mayo H; Ahern, Thomas P; MacLean, Charles D; Lahiri, Julie E; Alef, Matthew; Stanley, Andrew C; Steinthorsson, Georg; Bertges, Daniel J
The aim of this study was to assess postoperative opioid prescribing patterns, usage, and pain control after common vascular surgery procedures in order to develop patient centered best-practice guidelines. We performed a prospective review of opioid prescribing after seven common vascular surgeries at a rural, academic medical center from December 2016 to July 2017. A standardized telephone questionnaire was prospectively administered to patients ( n = 110) about opioid use and pain management perceptions. For comparison we retrospectively assessed opioid prescribing patterns ( n = 939) from July 2014 to June 2016 normalized into morphine milligram equivalents (MME). Prescribers were surveyed regarding opioid prescription attitudes, perceptions, and practices. Opioids were prescribed for 78% of procedures, and 70% of patients reported using opioid analgesia. In the prospective group, the median MMEs prescribed were: VEIN (31, n = 16), CEA (40, n = 14), DIAL (60, n = 17), EVAR (108, n = 8), INFRA (160, n = 16), FEM TEA (200, n = 11), and OA (273, n = 4). The median proportion of opioids used by patients across all procedures was only 30% of the amount prescribed across all procedures (range 14–64%). Patients rated the opioid prescribed as appropriate (59%), insufficient (16%), and overprescribed (25%), and pain as very well controlled (47%), well controlled (47%), poorly controlled (4%), and very poorly controlled (2%). In conclusion, we observed significant variability in opioid prescribing after vascular procedures. The overall opioid use was substantially lower than the amount prescribed. These data enabled us to develop guidelines for opioid prescribing practice for our patients.